The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0102-86502011000700012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rut-bpy (Cis-[Ru(bpy)2(SO3)(NO)]PF 6), a novel nitric oxide donor, in L-NAME-induced hypertension in rats

Abstract: PURPOSE:To evaluate the effect of Rut-bpy (Cis-[Ru(bpy) 2 (SO 3 )(NO)]PF 6 ), a novel nitric oxide donor in N -nitro-L-arginine methyl ester (L-NAME)-induced hypertensive rats. METHODS: Twenty-four male Wistar rats were randomly assigned to four groups (n=6), named according to the treatment applied (G1-Saline, G2-Rut-bpy, G3-L-NAME and G4-L-NAME+Rut-bpy). L-NAME (30 mg/Kg) was injected intraperitoneally 30 minutes before the administration of Rut-bpy (100 mg/Kg). Mean abdominal aorta arterial blood pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Many preclinical studies have been performed to support this concept. An NO donor similar to RuBPY, called Rutbpy (Cis-[Ru(bpy) 2 (SO 3 )(NO)]PF 6 ) induced stabilization in BP in anesthetized hypotensive Wistar rats [260]. Cerqueira et al (2008) studied two related nitrosyl-ruthenium complexes, named cis-[Ru(bpy) 2 (SO 3 )(NO)]PF-6-9 (FONO1) and trans-[Ru(NH 3 )4(caffeine)(NO)]C1 3 (LLNO1), which demonstrated a potent vasodilator effect in rabbit corpus cavernosum [261], corroborating the vasodilator potential of these drugs.…”
Section: Metal-based Drugs As No Donorsmentioning
confidence: 99%
“…Many preclinical studies have been performed to support this concept. An NO donor similar to RuBPY, called Rutbpy (Cis-[Ru(bpy) 2 (SO 3 )(NO)]PF 6 ) induced stabilization in BP in anesthetized hypotensive Wistar rats [260]. Cerqueira et al (2008) studied two related nitrosyl-ruthenium complexes, named cis-[Ru(bpy) 2 (SO 3 )(NO)]PF-6-9 (FONO1) and trans-[Ru(NH 3 )4(caffeine)(NO)]C1 3 (LLNO1), which demonstrated a potent vasodilator effect in rabbit corpus cavernosum [261], corroborating the vasodilator potential of these drugs.…”
Section: Metal-based Drugs As No Donorsmentioning
confidence: 99%
“…In addition, other NO donors have been developed, which promise advantages over the previous ones, such as spontaneous release of NO under controlled rates. In the literature, we can find descriptions of a variety of these, i.e., donors with higher levels of NO release without being photosensitive or releasing cyanide: for example, Rut-bpy (Cis-[Ru(bpy) 2 (SO 3 )(NO)]PF 6 ) (29) and/or donors with protection against hydrogen peroxide-mediated cytotoxicity diethylamine (DEA/NO) and propylamine propylamine (PAPA/NO) (30). The amount and duration of NO release depend on the pharmacological properties of each donor.…”
Section: Donors and Inhibitors Of Nomentioning
confidence: 99%
“…We have previously demonstrated that mice treated with Cis-[Ru(bpy) 2 (NO)SO 3 ](PF 6 ) are more resistant to Paracoccidioidomycosis (PCM) infection, thus, presenting prolonged survival with reduced leukocyte recruitment and TNF-α production in the lung and liver as well as increased production of the anti-inflammatory cytokine IL-10 (Pavanelli et al, 2011). This compound has exhibited interesting biological behavior with promising therapeutical potential such as in brain ischemia/reperfusion (Campelo et al, 2012) and cardiovascular agent (Campelo et al, 2011). Recently, it was showed this ruthenium-based NO-donor can efficiently release nitric oxide upon reaction with thiols, such as glutathione (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%